An Analytically and Diagnostically Sensitive RNA Extraction and RT-qPCR Protocol for Peripheral Blood Mononuclear Cells - Browne, Daniel J.; Brady, Jamie L.; Waardenberg, Ashley J.; Loiseau, Claire; Doolan, Denise L. (Frontiers in Immunology, 2020)
Reliable extraction and sensitive detection of RNA from human peripheral blood mononuclear cells (PBMCs) is critical for a broad spectrum of immunology research and clinical diagnostics. RNA analysis platforms are dependent upon high quality and high quantity mRNA, but this can be challenging with human samples and limited PBMC numbers. We provide herein a critical evaluation of the current generation of RNA-based kits for PBMCs and present a reverse transcription quantitative PCR (RTqPCR) assay optimized for both analytically and diagnostically sensitive cell-based RNA-based applications. Specifically, four RNA extraction kits, four SYBR master-mix kits, and four reverse transcription kits were tested. RNA extraction and RTqPCR reaction efficiency were evaluated with commonly used reference and cytokine genes. Significant variation in RNA expression of reference genes was apparent, and absolute quantification based on cell number was established as an effective RTqPCR normalization strategy. We defined an optimized RNA extraction and RTqPCR protocol with an analytical sensitivity capable of single cell RNA detection. The diagnostic sensitivity of this assay was sufficient to show a CD8+ T cell epitope hierarchy with as few as 1x104 cells. Finally, we compared our optimized RNA extraction and RTqPCR protocol with current best-practice immune assays and demonstrated that our assay is a sensitive alternative to protein-based assays, especially with limited PBMCs number. This protocol with high analytical and diagnostic sensitivity has broad applicability for both primary research and clinical practice.